WERNICKE ENCEPHALOPATHY FOLLOWING BARIATRIC SURGERY: CASE REPORT - L.R. AKHMADEEVA; O.V. GALIMOV; D.E. BAYKOV; Z.F. MAVLYANOVA; O.A. KIM; E.M. MAMYTOVA (Avicenna Tajik State Medical University, 2024)
Objective: To review the signs and symptoms of Wernicke encephalopathy (WE) after bariatric surgery based on 2 case reports and a literature data analysis. Methods: We present two case reports of WE. In these patients, thiamine deficiency developed due to bariatric gastric surgery, which was performed to treat class III obesity, formerly known as morbid obesity. The patients underwent comprehensive physical and neurological examinations; clinical, laboratory, and instrumental data were collected from medical records and analyzed. The researchers also performed a computerized search using the keywords "Wernicke encephalopathy after bariatric surgery" to find relevant publications in the PubMed/Medline, Scopus, and Web of Science databases. Results: The presented acute neurological condition related to vitamin B1 deficiency in two patients after undergoing a weight loss surgery, specifically a mini-gastric bypass. The clinical picture in one patient was dominated by memory impairment, ataxic, and polyneuritic syndrome, while in the other, it was only polyneuritic syndrome. Conclusion: The initial symptoms of WE are often overlooked, leading to the progression of the disease with the development of severe neurological deficits. To prevent the progression of encephalopathy, it is necessary to begin treatment with high doses of parenteral thiamine replacement therapy as early as possible.